Neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule 1 (KIM-1) as predictors of incident CKD stage 3: the Atherosclerosis Risk in Communities (ARIC) Study - Bhavsar, Nrupen A; Köttgen, Anna; Coresh, Josef; Astor, Brad C (American journal of kidney diseases, 2012)
Identifying individuals at risk of chronic kidney disease (CKD) is critical for timely treatment initiation to slow progression of the disease. Neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule 1 (KIM-1) are known biomarkers of acute kidney injury, but it is unknown whether these markers are associated with incident CKD stage 3 in the general population. Matched case-control study. African American and white participants from the Atherosclerosis Risk in Communities (ARIC) Study who at baseline had an estimated glomerular filtration rate (eGFR) ≥60 mL/min/1.73 m(2) and urinary albumin-creatinine ratio ≤30 mg/g. 143 controls were matched for age, sex, and race to 143 cases of incident CKD stage 3 after 8.6 years of follow-up. Quartile of NGAL and KIM-1. Incident CKD stage 3 (eGFR <60 mL/min/1.73 m(2) at follow-up and a decrease in eGFR from baseline to follow-up ≥25%). Both NGAL (P = 0.05) and KIM-1 levels (P < 0.001) were correlated positively with baseline urinary albumin-creatinine ratio; neither was associated with baseline eGFR. Participants with NGAL concentrations in the fourth quartile had more than 2-fold higher odds (adjusted OR, 2.11; 95% CI, 0.96-4.64) of incident CKD stage 3 compared with participants in the first quartile after multivariable adjustment (P-trend = 0.03). Adjustment for urinary creatinine and albumin levels resulted in a nonsignificant association (highest quartile adjusted OR, 1.52; 95% CI, 0.64-3.58; P = 0.2). No significant association between KIM-1 level and incident CKD was observed in crude or adjusted models. The relatively small sample size of the study limits precision and power to detect weak associations. Higher NGAL, but not KIM-1, levels were associated with incident CKD stage 3. Adjustment for urinary creatinine and albumin concentration attenuated this association. Additional studies are needed to confirm these findings and assess the utility of urinary NGAL as a marker of CKD risk.